2003
DOI: 10.1080/09537100310001612380
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of signaling underlying responses mediated by selective activation of the platelet thromboxane A 2 (TXA 2 ) receptor; pharmacological and kinetic studies in vitro

Abstract: Selective activation of the platelet TXA2 receptor is sufficient to mediate concurrent aggregation, deaggregation and shape change (SC) responses without activation of known Gi-coupled receptors (Platelets 2003; 14: 89). However, Gi-coupled receptor activation strongly influences the hemostasis response in vivo. This study investigated the modulatory effects of two signaling pathways related to Gi-coupled receptor activation, stimulation of phosphoinositide 3-kinases (PI3Ks) and inhibition of adenylyl cyclase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Promotion of platelet aggregation by sulprostone via an effect at EP3 receptors is already well established [7,10,11,[13][14][15][16][17], as is the ability of EP3 to link with adenylyl cyclase via G i and potentiate platelet aggregation via a decrease in cAMP [10,11,13,17]. We have demonstrated that sulprostone is able to decrease basal VASP phosphorylation and the concentrations needed to bring this about compare very well with the concentrations required to potentiate platelet aggregation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Promotion of platelet aggregation by sulprostone via an effect at EP3 receptors is already well established [7,10,11,[13][14][15][16][17], as is the ability of EP3 to link with adenylyl cyclase via G i and potentiate platelet aggregation via a decrease in cAMP [10,11,13,17]. We have demonstrated that sulprostone is able to decrease basal VASP phosphorylation and the concentrations needed to bring this about compare very well with the concentrations required to potentiate platelet aggregation.…”
Section: Discussionsupporting
confidence: 60%
“…There is good evidence that potentiation of platelet function is via effects at EP3 receptors linked to G i and inhibition of adenylyl cyclase [7,10,11,[13][14][15][16][17]. It is currently believed that inhibition of platelet aggregation may be via interaction with IP receptors linked to G s and stimulation of adenylyl cyclase [10,11], although this is mainly based on experiments conducted using mouse platelets [10] and the involvement of other receptors has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…We compared the effectsofUDP-glucosewith thoseofthe EP 3 receptor agonist sulprostone, aprostaglandin E 2 (PGE 2 )analogue (18).The stimulated EP 3 receptor potentiates plateletfunction by coupling to inhibitoryGp roteins, whichr esults in inhibitiono fa denylate cyclase (19)(20)(21). Sulprostone has been shown to potentiate primarya ggregation responses caused by several primary plateletagonistsincluding ADP,plateletactivating factor (PAF), 11,9-epoxymethano PGH 2 (U-46619),c ollagen, thrombin receptor activating peptide (TRAP)a nd 5-hydroxytryptamine (18,(22)(23)(24). It wasusedhere as apositivecontrol for the studies on the functionalityofthe P2Y 14 receptor.…”
Section: Introductionmentioning
confidence: 99%